Behaviour of Nitrates under Different Land Uses - Narain, Pratap; Singh, Ravender (Indian Forester, 1985)
In a study conducted on three forest watersheds namely Sal' Eucalyptus and Brushwood on an agricultural land in Doon valley' higher nitrates were observed upto 20 cm soil depth' which decreased in deeper layers. Agricultural land revealed much higher levels of nitrates than forest land users' particularly in 0-10 cm depth. Thus agricultural fields when dressed with heavy doses of nitrogen fertilizer pose a serious threat to nitrate contamination. Amongst the forest watersheds' higher nitrates were recorded under Sal followed by Eucalyptus and then brushwood. Maximum amount of nitrates were observed in February sampling followed by September and June sampling. Nitrate contents was found to bear direct relationship between ph' organic carbon and moisture status in surface layers. The correlation coefficients and regression equations have been reported.